Spatiotemporal Dynamics of Emerging Foot-and-Mouth Disease, Bluetongue, and Peste Des Petits Ruminants in Algeria - Ilhem Zouyed; Sabrina Boussena; Nacira Ramdani; Houssem Eddine Damerdji; Julio A. Benavides; Hacène Medkour (Viruses, 2025)
Foot-and-mouth disease (FMD), bluetongue (BT), and Peste des Petits Ruminants (PPR) are major emerging and re-emerging viral infections affecting ruminants. These diseases can threaten livestock health, food security, and economic stability in low- and middle-income countries, including Algeria. However, their dynamics remain mostly unknown, limiting the implementation of effective preventive and control measures. We analyzed outbreak data reported by Algerian veterinary authorities and the WAHIS database from 2014 to 2022 for FMD; from 2006 to 2020 for BT; and from 2011 to 2022 for PPR to investigate their spatiotemporal patterns and environmental drivers. Over these periods, Algeria reported 1142 FMD outbreaks (10,409 cases; 0.16/1000 incidence), 167 BT outbreaks (602 cases; 0.018/1000), and 222 PPR outbreaks (3597 cases; 0.096/1000). Small ruminants were the most affected across all diseases, although cattle bore the highest burden of FMD. BT primarily impacted sheep, and PPR showed a higher incidence in goats. Disease peaks occurred in 2014 for FMD, 2008 for BT, and 2019 for PPR. Spatial analyses revealed distinct ecological hotspots: sub-humid and semi-arid zones for FMD and BT, and semi-arid/Saharan regions for PPR. These patterns may be influenced by species susceptibility, animal movement, trade, and climatic factors such as temperature and rainfall. The absence of consistent temporal trends and the persistence of outbreaks suggest multiple drivers, including insufficient vaccination coverage, under-reporting, viral evolution, and environmental persistence. Our findings underscore the importance of targeted species- and region-specific control strategies, including improved surveillance, cross-border coordination, and climate-informed risk mapping. Strengthening One Health frameworks will be essential to mitigate the re-emergence and spread of these diseases.